The Arabidopsis E3 ubiquitin ligase PUB4 regulates BIK1 and is targeted by a bacterial type‐III effector - Yu, Gang; Derkacheva, Maria; Rufián Plaza, José Sebastián; Brillada, Carla; Kowarschik, Kathrin; Jiang, Shushu; Debryshire, Paul; Ma, Miaomiao; DeFalco, Thomas A; Morcillo, Rafael J; Stransfeld, Lena; Wei, Yali; et al. (EMBO Press, 2022)
Plant immunity is tightly controlled by a complex and dynamic regulatory network, which ensures optimal activation upon detection of potential pathogens. Accordingly, each component of this network is a potential target for manipulation by pathogens. Here, we report that RipAC, a type III‐secreted effector from the bacterial pathogen Ralstonia solanacearum, targets the plant E3 ubiquitin ligase PUB4 to inhibit pattern‐triggered immunity (PTI). PUB4 plays a positive role in PTI by regulating the homeostasis of the central immune kinase BIK1. Before PAMP perception, PUB4 promotes the degradation of non‐activated BIK1, while after PAMP perception, PUB4 contributes to the accumulation of activated BIK1. RipAC leads to BIK1 degradation, which correlates with its PTI‐inhibitory activity. RipAC causes a reduction in pathogen‐associated molecular pattern (PAMP)‐induced PUB4 accumulation and phosphorylation. Our results shed light on the role played by PUB4 in immune regulation, and illustrate an indirect targeting of the immune signalling hub BIK1 by a bacterial effector.
Keywords: Inmunología vegetal; BIK1; PAMP-triggered immunity; Ralstonia solanacearum; PUB4